Investigation of the effects of the program utilization of the museums for pre-school education on 6 year-old children - ABACI, OYA (ELSEVIER SCIENCE BV, 2010)
This research has been supported by Marmara University Scientific Research Project Committee under project number EGT-C-YLP-171108-0271. The research aimed to determine the effects of the program Utilization of Museums for Pre-School Education which was carried out according to the social-emotional and cognitive field gains determined by the education program of Ministry of Education on 6 year-old children continuing to pre-school educational institution. The research was carried out in three stages as pre-visit, visit and post-visit to the museums where various educational techniques were used. Educational program set on the themes of sheltering, clothing and intercommunication were applied on experimental group and the control group of students. Control group were only taken to the museums and not involved in the program. Statistical analyses revealed that the experimental group was more successful than the control group. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Museum; museum education; pre-school education; past concept; sheltering; clothing; intercommunication